Mock accreditation - Office of the Vice President for Academics, De La Salle University, Manila (Animo Repository, 1997)
The Office of the Vice President for Academics (VPA) formed a team composed of 7 faculty members to conduct a mock accreditation on July 18-19, in preparation for the Philippine Accrediting Association of Schools, Colleges, and Universities (PAASCU) visit on November 14 and 15. The PAASCU will evaluate the graduate programs of the CLA, COS and CED.